Relationship between systolic blood pressure and all-cause mortality: a prospective study in a cohort of Chinese adults - Chunsheng Li; Youren Chen; Qiongbing Zheng; Weiqiang Wu; Zhichao Chen; Lu Song; Shasha An; Zhifang Li; Shuohua Chen; S. L. Wu (BMC Public Health, 2018)
Abstract Background The association between systolic blood pressure (SBP) and all-cause mortality in Chinese adults remains unclear. This study aimed to identify the relationship of SBP with all-cause mortality in Chinese men and women. Methods One hundred twenty-one thousand eighty-two employees of the Kailuan Group Corporation, aged 18 or older, who participated in physical examination from 2006 to 2007 or from 2008 to 2009, were enrolled and followed up for all-cause mortality. The information used to ascertain the outcome of death during follow-up was extracted from provincial vital statistics offices, hospitalization records from the 11 hospitals, or medical records from medical insurance companies. Results The average age was 50.06 ± 12.85 in the overall sample. Over 7 years of follow-up, 5945 participants, including 5520 men and 425 women had all-cause mortality. After multivariate adjustment, men in SBP group of <100, 120–139, 140–159, 160–179 and ≥180 mmHg had hazard ratios (HR) of 1.46 (1.14–1.86), 1.14 (1.04–1.26), 1.29 (1.16–1.44), 1.57 (1.38–1.79) and 2.07 (1.76–2.43), respectively, and displayed significantly increased risk of all-cause mortality compared to those with SBP in the range of 100–119 mmHg. Compared with the group of 100–119 mmHg, women in SBP group of 140–159, 160–179 and ≥180 mmHg had significantly greater risk with HRs of 1.44 (95% CI, 1.01–2.07), 1.63 (95% CI, 1.04–2.55) and 2.31 (95% CI, 1.27–4.20). Conclusions Either lower (<100 mmHg) or higher (>120 mmHg) SBP was associated with an increased all-cause mortality risk and a J-shaped relationship was observed between SBP and all-cause mortality in men. Only SBP exceeding 140 mmHg was related to a higher risk in women. The relationship between SBP and all-cause mortality among Chinese adults may differ by sex.